Development and Validation of an IL6/JAK/STAT3-Related Gene Signature to Predict Overall Survival in Clear Cell Renal Cell Carcinoma - Zhan, Chuanchuan; Xu, Chao; Chen, Jiajun; Shen, Chong; Li, Jinkun; Wang, Zichu; Ying, Xiangrong; Luo, Zhengang; Ren, Yu; Wu, Gangfeng; Zhang, Haojie; Qian, Manfei (Frontiers in Cell and Developmental Biology, 2021)
Background: In predictive prognosis accuracy of clear cell renal cell carcinoma (ccRCC), traditional clinicopathological features (TNM, pathology grade) are often insufficient. The IL-6/JAK/STAT3 pathway is aberrantly hyperactivated in many types of cancer, and such hyperactivation is generally associated with a poor clinical prognosis which is revealed to act as a promising prognosis indicator. The relation between IL-6/JAK/STAT3 pathway and ccRCC is still unknown. Methods: We evaluated the levels of various hallmarks of cancer and filtered out the promising risk hallmarks in ccRCC. Subsequently, via weighted correlation network analysis and Cox regression analysis, a prognosis model based on promising risk hallmarks-related genes was established. Besides, we constructed a nomogram based on the previous model with traditional clinicopathological features to improve the predictive power and accuracy. Results: The IL-6/JAK/STAT3 pathway was identified as the promising risk hallmarks in ccRCC and the pathway-related prognosis model was constructed with five genes. Also, the nomogram we constructed showed the strongest and most stable survival predictive ability. Conclusions: our study would provide new sights for guiding individualized treatment of ccRCC patients.